Accounting undergraduates’ perspectives on integrating forensic accounting into the curriculum in Sri Lanka - Seneviratne, S M Chaturika; Dharmasena, S. D. Thamali Navangana (International Journal of Financial, Accounting, and Management, 2023)
Purpose: This study examines the current level of forensic accounting education in Sri Lanka and its level of sufficiency from the viewpoint of accounting undergraduates studying in Sri Lankan government universities. Research methodology: Data were collected through a self-administered questionnaire targeting third and fourth-year accounting undergraduates of Sri Lankan government universities. To achieve the research objectives, descriptive statistics were used as analytical tools. Results: The study revealed that existing auditing course modules and stand-alone forensic accounting course units do not adequately cover forensic accounting topics in response to the rising demand for forensic accountants' services in Sri Lanka. Sri Lankan government universities are required to restructure the integration of forensic accounting education with greater coverage. Moreover, as per accounting undergraduates, the precise method of covering forensic accounting within accounting education would be to introduce a separate degree program that covers all forensic accounting discussions. Limitations: The main limitation of this study is that it focuses only on the perspectives of government university undergraduates. Perceptions of accounting undergraduates in private universities and professional qualification institutions that offer accounting degree programs were not considered. Contribution: This study provides insights for university administrators on how to integrate forensic accounting into the accounting curriculum. Moreover, the suggested modifications will provide undergraduates with the skills required to practice forensic accounting after graduation.